Attitudinal Disposition of Teachers towards counsellors: Roles in Secondary Schools in Delta North Senatorial District of Delta State (Journal of Guidance and Counselling Studies, 2022)
The study focused on the attitudinal dispositions of teachers towards counsellors’ roles in secondary schools in Delta North Senatorial District of Delta State. Four research questions guided the study. The descriptive survey design was utilized for the study. The design was considered appropriate since data were obtained from teachers in different schools that constituted the areas of study. The population of this study consisted of all secondary school teachers in Delta North Senatorial District of Delta State. The sample for this study consisted of 160 teachers in Delta North Senatorial District of Delta North Senatorial District of Delta State. The researcher employed the purposive and random sampling techniques. The instruments used for the study was titled Teachers Attitude toward Counselors’ Inventory (TATCI). The data collected were collated, coded and analyzed with the mean, descriptive statistic, the t-test statistics and the One Way ANOVA because of their appropriateness to the hypotheses. The finding revealed a slightly positive attitude of teachers’ towards counsellors’ roles in secondary Schools in Delta North Senatorial District of in Delta North Senatorial District of Delta State, non-significant difference in hypotheses one and two and a significant difference in hypothesis three. Conclusion was drawn and recommendations made, which include among others that should organise workshops, conferences and seminars to sensitise teachers, students and parents on issues relating to counsellors’ roles in schools. Ministry of Education should begin to incorporate counseling programmes into all schools, and categorically state their objectives in the school system.